Amino modification enhances reproductive toxicity of nanopolystyrene on gonad development and reproductive capacity in nematode Caenorhabditis elegans. (November 2019) - Qu, Man; Qiu, Yuexiu; Kong, Yan; Wang, Dayong
Abstract: Although amino modified nanopolystyrene could cause toxicity on environmental organisms, the effect of amino modification on nanopolystyrene toxicity is still largely unclear. We here employed Caenorhabditis elegans as an animal model to compare the effects between pristine and amino modified nanopolystyrene particles in inducing reproductive toxicity. Nanopolystyrene (35 nm) could cause the damage on gonad development as indicated by the endpoints of number of total germline cells, length of gonad arm, and relative area of gonad arm. Nanopolystyrene exposure also reduced the reproductive capacity as reflected by the endpoints of brood size and number of fertilized eggs in uterus. Moreover, amino modification enhanced nanopolystyrene toxicity on both the gonad development and the reproductive capacity. Additionally, induction of germline apoptosis and formation of germline DNA damage contributed to the enhancement of nanopolystyrene toxicity in reducing reproductive capacity by amino modification. Our results highlight the potential environmental risk of amino modified nanopolystyrene in inducing reproductive toxicity on gonad development and reproductive capacity of environmental organisms. Graphical abstract: Amino modification effectively enhanced the reproductive toxicity on both gonad development and reproductive capacity in nanopolystyrene exposed nematodes. Image 1 Highlights: We compared reproductive toxicity between pristine and amino-modified nanopolystyrene. Nanopolystyrene (35 nm) caused damage on gonad development and reproductive capacity. Amino modification enhanced the nanopolystyrene toxicity in nematodes. Abstract : Amino modification enhanced the reproductive toxicity of nanopolystyrene on both gonad development and reproductive capacity in nematodes.